Localization of nucleic acids in the nucleoli of oocytes and early embryos of mouse and hamster: an autoradiographic study - Kopecný, V; Landa, V; Pavlok, A (Molecular reproduction and development, 1995)
Mouse preovulatory oocytes, zygotes, parthenogenetically activated pronuclear oocytes, and early embryos, as well as hamster zygotes, were analyzed, by autoradiography, for the distribution of either "maternal" or newly synthesized RNAs. Early mouse embryos were also examined for the distribution of newly replicated DNA. Special attention was attributed to NLBs in oocytes or to NPBs in early embryos. In mouse oocytes, [5-(3)H]uridine radioactivity accumulated (after a 2-hr pulse in vitro, in addition to other nuclear compartments, in the central compact material of the NLBs. There was no cytoplasmic labeling. In all parthenogenetic pronuclear embryos developed from similarly labeled oocytes, this label was distinctly detectable in the central compact material of the NPBs; less intensive labeling was seen in the nucleoplasm and cytoplasm. On the contrary, the central compact part of the mouse NPB did not show labeling in DNA after a continuous culture with [6-(3)H]thymidine. In mouse and hamster pronuclear zygotes, convincing evidence was obtained for a lack of any newly synthesized nucleic acids in the compact material of NPBs using 4- to 10-hr culture with [8-(3)H]adenosine. Based on these data, it was shown that the NLBs of oocytes or NPBs of early embryos probably contain RNAs synthesized during the last stages of antral follicle oocyte differentiation. This unique pathway of RNAs in the oocyte-embryo system may explain the specific morphology of both oocyte and early embryo "nucleoli".
Keywords: křečci praví; Zygote; partenogeneze; Blastocyst; RNA; zygota; nukleové kyseliny; Oogenesis; Cell Nucleolus; zvířata; myši; myši inbrední C57BL; oogeneze; Mice; oocyty; blastocysta; DNA Replication; replikace DNA; Cytoplasm; Mice, Inbred C57BL; Nucleic Acids; Cricetinae; cytoplazma; Animals; Oocytes; Parthenogenesis; buněčné jadérko